Carotid Intima-Media Thickness and Cardiovascular Risk Factors - Santos, Vitorino Modesto dos; Modesto, Laura Campos (International Journal of Medical Students, 2020)
Albers SS et al. reviewed carotid artery variation in the development of atherosclerotic carotid artery disease (Int J Med Students. 2019 Sep-Dec;7(3):82-91) commenting on changes from birth to older ages that can contribute to disorders of intramural elastin even in absence of disease. Considering the coexistence of traditional risk factors of atherosclerosis, additional comments are posed about measurements of carotid intima-media thickness in patients with obesity, chronic renal failure, and secondary hyperparathyroidism. The authors emphasized the need for further research to validate preventive procedures initiating since prenatal.